2016
DOI: 10.17159/i65a06
|View full text |Cite
|
Sign up to set email alerts
|

Different rules for different teachers: teachers’ views of professionalism and accountability in a bifurcated education system1

Abstract: This paper reports the initial results from a representative survey of teachers in the WesternCape regarding their views of professionalism and accountability. This is the first survey ofits kind in South Africa. Preliminary analysis of the data from 115 public schools suggeststhat teachers at no-fee schools, who are predominantly black women, report facing thegreatest institutional burdens and the greatest need for institutional support, particularlyfrom the state. Related to this, they tend to stress pastora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Although literacy and numerical scores for white people are higher than those of black people in schools meant for blacks (Hoffman et al, 2016), this research shows that if STEM education is taught even among poor black communities, the knowledge can be comprehended and accepted by all irrespective of the background of the learner. More so, the researcher demonstrated that the learning theory of the constructivistinterpretive approach could be applied in a society where learners are allowed to think and create ideas and knowledge independently so they can solve life problems (McLeod, 2023).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Although literacy and numerical scores for white people are higher than those of black people in schools meant for blacks (Hoffman et al, 2016), this research shows that if STEM education is taught even among poor black communities, the knowledge can be comprehended and accepted by all irrespective of the background of the learner. More so, the researcher demonstrated that the learning theory of the constructivistinterpretive approach could be applied in a society where learners are allowed to think and create ideas and knowledge independently so they can solve life problems (McLeod, 2023).…”
Section: Resultsmentioning
confidence: 67%
“…Further government intervention led to the construction of modern houses and the provision of social amenities for the people of Cosmo City. There is also a high population of African migrants in Cosmo City, which has led to high competition for resources, including the provision of education, leading to its scarcity (Hoffman et al, 2016). Public schools in Cosmo City are finding it difficult to accommodate all students and lagging in the number of science-based teachers they have.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the internal regulation at the meso school level, the school culture and management at school level obviously regulates novice teachers' work in vital ways that cannot be addressed directly by initial teacher education. The distribution of well-qualified teachers is uneven across schools given the bi-furcated education system as Hoffman et al (2016) have noted. Fee-paying schools tend to have better-qualified teachers whose organisational assets bring better mentoring possibilities for novice teachers as a well as a reservoir of specialised knowledge, skills, and dispositions (Chisholm et al, 2005;Sayed, 2016;Shalem & Hoadley, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, uneven learning outcomes strongly correlate with the bifurcated schooling system, which reflects students' "race" and class. Higher student achievement is generally seen in the 20% of schools that charge school fees and thus serve the middle and upper classes (Hoffman, Sayed, and Badroodien 2016). Thus, teachers' role in teaching for social justice and being able to recognise both individual and social barriers to learning is vital.…”
Section: Contextual Specialisationmentioning
confidence: 99%